Programa De Atención E Intervención Psicosocial Orientado A La Construcción De Habilidades Psicosociales Para La Vida Desde La Gestión Del Riesgo Frente Al Estrés Laboral En Golden Flash (2021)
Studying the dynamics and natural organizations of work today has begun to be of great importance. Through time, the advances to improve the quality of life of the being have increased productivity and actions at the corporate level to provide services or some type of product to society, which means improving the work environment in favor of the health of workers and the benefit of the companies themselves (Velasco, 2012)